Transformed extracellular vesicles with high angiogenic ability as therapeutics of distal ischemic tissues - Nhat-Hoang Ngo; Yun-Hsuan Chang; Cat-Khanh Vuong; Toshiharu Yamashita; Mana Obata-Yasuoka; Hiromi Hamada; Motoo Osaka; Yuji Hiramatsu; Osamu Ohneda (Frontiers in Cell and Developmental Biology, 2022)
Introduction: The therapeutic effects of endothelial progenitor cells (EPC) in neovascularization have been suggested; however, to date, few studies have been conducted on the ability of EPC-derived extracellular vesicles (EV) to rescue the ischemic tissues. In order to examine the functional sources of EV for cell-free therapy of ischemic diseases, we compared the functions of EPC-EV and those of Wharton’s Jelly-derived mesenchymal stem cell (WJ-EV) in the flap mouse model.Results and conclusion: Our results demonstrated that in the intravenous injection, EPC-EV, but not WJ-EV, were uptaken by the ischemic tissues. However, EPC-EV showed poor abilities to induce neovascularization and the recovery of ischemic tissues. In addition, compared to EPC-EV, WJ-EV showed a higher ability to rescue the ischemic injury when being locally injected into the mice. In order to induce the secretion of high-functional EPC-EV, EPC were internalized with hypoxic pre-treated WJ-EV, which resulted in a transformed hwEPC. In comparison to EPC, hwEPC showed induced proliferation and upregulation of angiogenic genes and miRNAs and promoted angiogenic ability. Interestingly, hwEPC produced a modified EV (hwEPC-EV) that highly expressed miRNAs related to angiogenesis, such as miR-155, miR-183, and miR-296. Moreover, hwEPC-EV significantly induced the neovascularization of the ischemic tissues which were involved in promoting the proliferation, the expression of VEGF and miR-183, and the angiogenic functions of endothelial cells. Of note, hwEPC-EV were highly uptaken by the ischemic tissues and showed a greater effect with regard to inducing recovery from ischemic injury in the intravenous administration, compared to EPC-EV. Therefore, hwEPC-EV can be considered a functional candidate for cell-free therapy to treat the distal ischemic tissues.